STUDI FENOMENOLOGI : PENGALAMAN PSIKOLOGIS MANTAN PEROKOK DALAM MENGHENTIKAN KEBIASAAN MEROKOK DI KOTA BUKITTINGGI - Silvia Intan Suri (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Based on some experience of smokers, smoking habit can be stopped in some time. However, notall that successful in stopping the habitin a long period of time. Still a little research to see how theexperience of the former smokers who successfully stopped smoking habit. This research aims toexplore in depth the psychological experience of former smokers in stopping smoking habit. Thisresearch uses qualitative research methods with the phenomenology of approach. Dataobtained with the in-depth interview against 5 persons participating which have variation inthe length of time it has managed to stop smoking. Research results get some major aspect of thesuccessful. Response smokers in quitting smoking; the obstacles they face, the mechanismof motivation and koping used in stop smoking habit, and the changes to be felt after quitting. Thisresearch managed to identify some important aspects such as the strategies used and theunderlying motivation to stop smoking. Expected results of this research can be an inputfor smokers or health workers in providing support so that smokers can quit their habits for longperiods of time or permanently.Keywords: Experiences, Psychological, Former smoker